Lembar Kerja Peserta Didik Berbasis Kegiatan Transaksi Kewirausahaan Materi Sistem Persamaan Linier Dua Variabel - Supardi, Novitasari; Rinaldi, Achi; Rakhmawati M, Rosida (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to produce products in the form of LKPD SPLDV material, and Know the response of educators to LKPD on SPLDV material. The method of this research is Research and Development (R & D) based on ADDIE model Stages performed only from stage 1 to stage 5 that is from analysis, design, development, implementation, evaluation. The result of the material expert test on the content quality aspect obtained the average score of 3.67 with very good criteria, on the aspect of the accuracy of the scope obtained the average score of 3,167 with good criteria. Expert test media on LKPD size aspect got the average score 4 very interesting, skin design aspect LKPD got average score 3,66 with the good criterion, design aspect of LKPD got average score 3,4167 with good criterion. Expert tests obtained an average score of 3.22 with good criteria. In the small group trial of students in the attractiveness, test obtained an average score of 3.57 with interesting criteria, large group trials of students in the attractiveness test obtained an average score of 3.56 with interesting criteria. From some of the above data, it can be concluded that LKPD developed into good criteria and get a good response for the learners.